Fish oil enriched ω-3 fatty acids ameliorates protein synthesis/degradation imbalance, inflammation, and wasting in muscles of diet-induced obese rats. (December 2021) - Liu, Shing-Hwa; Chen, Yu-Ching; Tzeng, Huei-Ping; Chiang, Meng-Tsan
Graphical abstract: Highlights: Effects of fish oil (FO) on muscles in high-fat diet-induced obese rats were tested. Supplementation with 5% FO for 16 weeks prevented obesity and skeletal muscle loss. FO prevented muscle wasting via activating AKT/mTOR and AMPK/PGC-1α signals. FO improved protein synthesis/degradation imbalance and wasting in obese rat muscle. Abstract: We investigated the effects of long-term supplementation of omega-3 fatty acids-enriched fish oil (FO) on preserving muscle mass. We found that dietary supplementation with 5% FO has a direct impact on preventing obesity and skeletal muscle loss in rats fed a high-fat diet for 16 weeks. The increased protein expression for ubiquitin ligases atrogin-1 and muscle RING-finger protein 1 (MuRF1) and the autophagy-related protein, PTEN-induced putative kinase 1 (PINK1) in muscles were both abrogated by FO. The AKT and mammalian target of rapamycin (mTOR) phosphorylation and the AMP‐activated protein kinase (AMPK)/peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α) signaling activation in muscles were up-regulated by FO. FO supplementation effectively reversed the increased plasma TNF-α levels and NF‐κB activation in muscles. These results suggest that FO supplementation prevents skeletal muscle wasting under obesity through activating AKT/mTOR and AMPK/PGC-1α signals and blocking NF-κB-mediated inflammatory pathway to improve the balance between protein synthesis and degradation.